2016
DOI: 10.1007/s00429-016-1299-5
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytic and neuronal localization of kynurenine aminotransferase-2 in the adult mouse brain

Abstract: During catabolism of tryptophan through the kynurenine (KYN) pathway, several endogenous metabolites with neuromodulatory properties are produced, of which kynurenic acid (KYNA) is one of the highest significance. The causal role of altered KYNA production has been described in several neurodegenerative and neuropsychiatric disorders (e.g., Parkinson's disease, Huntington's disease, schizophrenia) and therefore kynurenergic manipulation with the aim of therapy has recently been proposed. Conventionally, KYNA i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 50 publications
3
18
0
Order By: Relevance
“…Reduced cerebral KA production in PD and AD could also be the consequence of cell-specific changes in the brain. Astrocytes are considered the primary source of extracellular KA concentrations (Guillemin et al 2001;Kiss et al 2003) and studies in rodents showed that kynurenine aminotransferase II (KATII)the enzyme that converts Kyn to KAwas strongly localized to astrocytes (Guidetti et al 2007;Her edi et al 2017;Song et al 2018). In response to activated microglia, astrocytes can change their molecular behavior during diseases of the brain (Liddelow et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Reduced cerebral KA production in PD and AD could also be the consequence of cell-specific changes in the brain. Astrocytes are considered the primary source of extracellular KA concentrations (Guillemin et al 2001;Kiss et al 2003) and studies in rodents showed that kynurenine aminotransferase II (KATII)the enzyme that converts Kyn to KAwas strongly localized to astrocytes (Guidetti et al 2007;Her edi et al 2017;Song et al 2018). In response to activated microglia, astrocytes can change their molecular behavior during diseases of the brain (Liddelow et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In schizophrenia, there is hypofunction of NMDA receptors, which leads to a decrease in prefrontal cortex functions (Herédi et al, 2017). Weakened prefrontal cortex function associated with NMDA receptor hypofunction may be involved in the development of negative and cognitive symptoms.…”
Section: Glutamate Systemmentioning
confidence: 99%
“…It is produced by kynurenine aminotransferases (KATs) and can influence glutamatergic neurotransmission at several levels and have exerted neuroprotective effects in several paradigms [5,202,210,267,268]. KYNA is capable of exerting a wide-spectrum of endogenous antagonistic effects at ionotropic excitatory amino acid receptors [269].…”
Section: Kynurenic Acidmentioning
confidence: 99%